PENGARUH PELAPUKAN TERHADAP REKAHAN BATUAN UTUH MELALUI PENGUJIAN DI LABORATORIUM - Karmila Laitupa (INTAN Jurnal Penelitian Tambang, 2020)
Cracked rock is an indication of instability in underground excavations due to being under high-pressure conditions that causes new cracks to appear by forming cracks in the walls of holes or tunnels. The cracking process can be influenced by environmental conditions around the rock. Therefore, this study aims to analyze the effects of weathering on cracks and other characteristics in intact rock. Petrographic observations indicate differences in the presentation of rock mineral preparation in the six samples. Changes in the preparation of primary rocks are plagioclase minerals (32% -39%) and hornblende minerals (12% -20). While the opaque mineral (3% -5%) as a change from the mineral hornblende, volcanic glass (8% -21%) has partially decayed into clay and plagioclase microlites (17%). The results of the uniaxial compressive strength test suggested that the crack initiation stress value of rock samples KA2, KA3, BT1, BE2, TS2, and TD3 are 22.55 MPa, 35.07 MPa, 20.04 MPa, 50.08 MPa, 34, 92 MPa and 105.22 MPa. The rock strength of the six rock samples is 61.92 MPa, 47.6 MPa, 86.43 MPa, 89.39 MPa, 88.54 MPa, and 120.25 MPa, respectively. The results also showed a tendency to increase fracture initial stress (crack initiation) along with the increase in uniaxial compressive strength values. the stronger the pressure of the withstanding test, the greater the initial stress of the crack (crack initiation). This is caused by weathering which can reduce the elasticity of rocks that increases surface tension. Weathering plays an important role in changing the initial stress value of fractures and the strength of intact rock. The higher the weathering the smaller the rock strength and the initial stress value of the crack. Weathering due to degradation and mineralogy changes in intact rock samples has an impact on the characteristics of intact rock. This is shown in changes in the value of the content weight, porosity, rock strength, rock fracture, Modulus Young and Poisson Ratio decreases with increasing weathering.